Threads of Tradition: Native American Women’s Resistance and Resilience in Piatote’s “Beading Lesson” - Pukan, Elisabeth Oseanita; Rosiandani, Ni Luh Putu; Iskarna, Tatang (Universitas Sanata Dharma, 2023)
Resistance literature’s significance to empower the weak cannot be overemphasized. This article examines “Beading Lesson” by Native American (NA) women author, Beth Piatote. The short fiction highlights the importance of NA women’s roles within their communities. Utilizing the Indigenous feminist framework, this study applies seven analytical categories of resistance by Baaz et al. and integrates Southwick et al.’s concepts of resilience to examine how the narrator navigates through historical trauma and hardships. In the narrative, issues such as tumultuous relations with the U.S. government, exploitation, incarceration, cultural erasure, and change of gender roles, are brought up in the story through the light-toned monologue of an aunt, the narrator, who is teaching her niece how to bead. Contrasted to this backdrop of historical trauma and adversities is the narrator’s resistance and resilience embedded in her everyday actions. The findings revealed that the narrator employs discreet and non-confrontational forms of resistance demonstrated through routine activities such as beading, teaching, storytelling, and engaging in powwow rituals. These seemingly ordinary activities are actually powerful acts of resistance as they assert the narrator’s original gender role as keeper of tradition within the context of NA culture. The narrator’s resilience is firmly grounded in her strong sense of identity as an NA woman. By engaging in various forms of resistance, she not only challenges the oppressive system but also helps foster collective resilience in her community. As resistance literature, this short fiction reveals the multifaceted forms of resistance and resilience within NA communities.